Gender and Religion: A Survey - Sascha O. Becker; Jeanet Sinding Bentzen; Chun Chee Kok (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
This paper provides a survey of the literature on gender differences in religiosity and the influence of religion on gender-related economic and social outcomes. Part I examines why women tend to be more religious than men, discussing central explanations. Part II explores how religion impacts various gender-related outcomes, such as gender norms and attitudes, education, labor market participation, fertility, health, legal institutions and reforms, and discrimination. Within each domain, we distinguish between effects driven by individual religiosity (intensity of religious practice or belief) and those driven by their religious denomination. We synthesize findings from numerous studies, highlighting data sources, measures of religion and gender outcomes, and empirical strategies. We focus on studies with credible causal identification—such as natural experiments, instrumental variable approaches, and policy changes—to uncover the impact of religion on outcomes. Correlational studies are also reviewed to provide context. Across studies, the evidence suggests that religious teachings and participation often reinforce traditional gender roles, affecting women's education, labor force participation, and fertility choices, although there are important nuances and exceptions. We also document instances where secular reforms or religious movements have altered these outcomes. The survey concludes by identifying gaps in the literature and suggesting directions for future research. An important take-away from our review is that rigorous empirical studies are scarce, leaving room for novel causal studies in this field.
Keywords: Z12; J16; J24; I21; J13; Z13; 330; gender gap; religion; religiosity; gender norms; education; fertility; labor markets; cultural transmission